Allergic bronchopulmonary mycosis due to fungi other than Aspergillus: a global overview. (February 2014) - Chowdhary, Anuradha; Agarwal, Kshitij; Kathuria, Shallu; Gaur, Shailendra Nath; Randhawa, Harbans Singh; Meis, Jacques F.
Abstract Allergic bronchopulmonary mycosis (ABPM) is a hypersensitivity-mediated disease of worldwide distribution. We reviewed 143 reported global cases of ABPM due to fungi other than aspergilli. The commonest etiologic agent was Candida albicans, reported in 60% of the cases, followed by Bipolaris species (13%), Schizophyllum commune (11%), Curvularia species (8%), Pseudallescheria boydii species complex (3%) and rarely, Alternaria alternata, Fusarium vasinfectum, Penicillium species, Cladosporium cladosporioides, Stemphylium languinosum, Rhizopus oryzae, C. glabrata, Saccharomyces cerevisiae and Trichosporon beigelii. India accounted for about 47% of the globally reported cases of ABPM, attributed predominantly to C. albicans, followed by Japan (16%) where S. commune predominates, and the remaining one-third from the USA, Australia and Europe. Notably, bronchial asthma was present in only 32% of ABPM cases whereas its association with development of allergic bronchopulmonary aspergillosis (ABPA) is known to be much more frequent. The cases reviewed herein revealed a median IgE value threefold higher than that of ABPA, suggesting that the etiologic agents of ABPM incite a stronger immunological response than that by aspergilli in ABPA. ABPM is currently underdiagnosed, warranting comprehensive basic and clinical studies in order to elucidate its epidemiology and to devise a more effective therapy.